Comparative Study of Lead (Pb) Levels on the Goats Liver at Industrial and Non-Industrial Areas Using Atomic Absorption Spectrophotometry Method - Chairuddin; PURBA, NORA MARIHOT; Bangun, Ahmad Darwin (Journal of Chemical Natural Resources, 2022)
The comparison of Lead in goat liver in an industrial and non-industrial area. The goat liver was drily digested, and then the ash of the goat liver dissolved with HNO3(p). Qualitative test using Inductively Coupled Plasma – Optical Emission (ICP – OES) where the sample results obtained I (Industrial area) = 0.088 ppm, sample II (Industrial area) = 0.080 ppm, sample III (Industrial area) = 0.086 ppm and sample IV (Non-Industrial area) = 0.022 ppm and Quantitative test determination of Pb content using Atomic Absorption Spectrophotometry (AAS) at a wavelength for Pb 217.0 nm. The result of the determination showed that the content in Lead of sample A (Non-Industrial Area) = 0.4585 mg/Kg, sample B (Non-Industrial Area) = 0.4490 mg/Kg, sample C (Industrial area) = 0.8761 mg/Kg and sample D (Industrial area) = 0.8622 mg/Kg. However, Pb of metal content fulfilled SNI 7387:2009 that 1.0 mg/Kg.